2017
DOI: 10.1016/j.phrs.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and pharmacologic insights on immune checkpoint inhibitors

Abstract: The concept of augmenting the immune system to eradicate cancer dates back at least a century. A major resurgence in cancer immunotherapy has occurred over the past decade since the identification and targeting of negative regulators with antibody therapies to augment the anti-tumor immune response. Unprecedented responses across a broad array of cancer types elevated this class of therapies to the forefront of cancer treatment. The most successful drugs to date target the cytotoxic T-lymphocyte-associated ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…33 Duokines are not restricted to cancer therapy but might also be beneficially applied in other indications, such as viral infections, especially those being latent or chronic in nature. 34,35 Because of their modular structure, the duokine strategy described here allows combining different members of the co-stimulatory TNFSF family and thus, enables to specifically tailor the immunological responses to the therapeutic requirements.…”
Section: Discussionmentioning
confidence: 99%
“…33 Duokines are not restricted to cancer therapy but might also be beneficially applied in other indications, such as viral infections, especially those being latent or chronic in nature. 34,35 Because of their modular structure, the duokine strategy described here allows combining different members of the co-stimulatory TNFSF family and thus, enables to specifically tailor the immunological responses to the therapeutic requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years some studies have reported the utility of KL 6 for the evaluation of DILD. KL 6 is typically elevated in patients with idiopathic interstitial pneumonia and in certain cases of cancer, and may therefore be useful for evaluating disease activity and clinical outcome in patients with ILD-IPF: it could predict the likelihood of radiation pneumonitis or lung toxicity induced by chemotherapy [15][16][17][18][19][20]. Recently, a similar predictive role of Surfactant Protein D (SP-D) for onset of ILD induced by anticancer agents was compared with KL 6 in an interesting case control study [18].…”
Section: Casementioning
confidence: 99%
“…Programmed death-ligand 1 (PD-L1) is a transmembrane protein that binds to the programmed death-1 receptor (PD-1) during immune system modulation. The PD-1 receptor is typically expressed on cytotoxic T-cells and other immune cells while PD-L1 ligand is typically expressed on normal cells [31]. Under normal conditions, cells use the PD-1/PD-L1 interaction as a mechanism of protection against immune recognition via inhibiting the action of T-cells thus downregulating the immune response such that inactive T-cells are exhausted, cease to divide and eventually die by programmed cell death or apoptosis [30].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, cells use the PD-1/PD-L1 interaction as a mechanism of protection against immune recognition via inhibiting the action of T-cells thus downregulating the immune response such that inactive T-cells are exhausted, cease to divide and eventually die by programmed cell death or apoptosis [30]. Studies have shown that numerous types of tumor cells upregulate the expression of PD-L1 as a mechanism to evade the immune response [31]. Activated T-cells recognize the PD-L1 marker on the tumor cell (similar to that of a normal cell) and render the cytotoxic T-cell inactive and thus the tumor cell escapes the immune cycle for elimination and is able to proliferate [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation